Konstruksi sosial gender di pesantren : studi kuasa kiai atas wacana perempuan - Marhumah, Ema, 1962- (Yogyakarta : Penerbit & distribusi, LKiS, 2011)
On gender equality in Islamic religious training center in Indonesia.
Revision of the author's thesis (doctoral) -- Universitas Islam Negeri Sunan Kalijaga, Yogyakarta, 2008.
Includes bibliographical references (pages 191-200) and index.
Keywords: Feminism -- Indonesia; Women in Islam -- Indonesia; Islamic religious education -- Indonesia